Sentinel lymph node biopsy for breast cancer using methylene blue: a new anatomical landmark involving intercostobrachial and medial pectoral nodes (Medical Journal of Indonesia, 2020)
BACKGROUND Sentinel lymph node biopsy (SLNB) using blue dye is becoming popular in Indonesia given that knowledge on new anatomical landmarks involving intercostobrachial and medial pectoral nodes have replaced the need for radioisotope tracers. This study aimed to evaluate the utility of the proposed landmark involving intercostobrachial and medial pectoral nodes to determine axillary lymph node status during SLNB. METHODS A prospective study was conducted involving 55 patients with early-stage breast cancer who had clinically negative lymph nodes (T1T2, cN0) between 2018 and 2019 at Cipto Mangunkusumo Hospital. During SLNB, methylene blue 1% was injected at the subareolar area to identify intercostobrachial and medial pectoral nodes followed by axillary lymph node dissection (ALND). Histopathological results of sentinel nodes (SNs) were then compared to those of other axillary nodes. RESULTS SNs were identified in 54 patients (98%), 33 (61%) of whom had both intercostobrachial and medial pectoral SNs. Among patients with SNs, there were 1 patient without intercostobrachial SNs, 10 patients without medial pectoral SNs, and 1 patient with medial pectoral SNs but no intercostobrachial SNs. Accordingly, SNs had a negative predictive value (NPV) of 96.77% for axillary metastasis (95% confidence interval = 81.5499.51), with a false negative rate of 4.7%. No serious adverse events was observed. CONCLUSIONS The high identification rate and NPV, as well as the low false negative rate of the new anatomical landmark involving intercostobrachial and medial pectoral nodes during SLNB, suggest its reliability in determining axillary lymph node status.